Terena e Guarani na reserva indígena de Araribá: um estudo etnográfico da aldeia Tereguá - Coelho, Márcio Oliveira de Castro (2016)
This dissertation is analytically the historical formation of the Indian Reserve Araribá located in the municipality of Avai (SP), focusing on the relationships that occur between Terena and Guarani groups that will lead to the formation of a village called Tereguá where, theoretically, individuals inhabit the mixing occurred between these ethnic groups. The reserve Araribá was created in 1913 by the official indigenous agency of the Brazilian state, first the Indian Protection Service - SPI (1910-1967) and then the National Indian Foundation - FUNAI (1967 onwards), on land belonging to the unoccupied calls state of São Paulo in territorialization process of the Guarani indigenous population that was scattered between the São Paulo west, north of Parana and east of Mato Grosso do Sul. Araribá reserve, initially occupied by Guarani families, eventually adding Terena families brought by SPI, from the 1930s, from Mato Grosso (South), and Brazilian regional were also incorporated by intermarriage. Currently, the reserve of 1.930 hectares, with a population of about 600 people, is divided into four villages: Kopenoti and Ekeruá occupied by Terena families; Nimuendajú occupied by families Guarani and Terena Tereguá occupied by families, Guarani and those in which there was a mix between these two ethnic groups. The sources used are literature and ethnographic, from a participant observation and conversations with the Indians during the research field. The work seeks to make an ethnography of Tereguá community, highlighting its historical formation and their relationships, established inside the reserve, with the other villages.